PREVALENSI BAKTERI Escherichia coli DAN Klebsiella pneumoniae PENGHASIL EXTENDED SPECTRUM BETA LACTAMASE (ESBL) YANG DIISOLASI DARI PASIEN PNEUMONIA DI RSUP SANGLAH PERIODE TAHUN 2019-2020 - Ida Ayu Santhi Pertiwi Manuaba; Ida Sri Iswari; Komang Januartha Putra Pinatih (Universitas Udayana, 2021)
Pneumonia infection is the sixth highest cause of death in general and the highest cause of death in infection cases, recorded as much as 2.1% of the pathogens that cause pneumonia infection is ESBL-producing bacteria. In general, Escherichia coli (E.coli) and Klebsiella pneumoniae (K.pneumoniae) are the most common bacteria found to be ESBL-producing bacteria. The aims of this study is to discover the prevalence of ESBL-producing in Escherchia coli and Klebsiella pneumoniae bacteria isolated from pneumonia patients at Sanglah General Hospital in 2019-2020 period of time. Method of this study is a cross-sectional descriptive study with a retrospective cross-sectional study approach. Data were taken retrospectively from the register database of the Clinical Microbiology Installation in Sanglah General Hospital. Sample for this research was derived from the results of antibiotics sensitivity tests on sputum isolated from patients with pneumonia infection. The prevalence of ESBL-producing Escherichia coli bacteria 93.3% was found higher than Klebsiella pneumoniae bacteria 69.2%. The highest finding was recorded in male patients and 15-64 years old. Based on the highest number of patients clinical diagnosis, it is found to be pneumonia in Escherichia coli and CAP in Klebsiella pneumoniae. The highest rates of patients are coming from Emergency Room. The result of antibiotic sensitivity test on Escherichia coli and Klebsiella pneumoniae producing ESBL were found the highest antibiotic sensitivity rates on ertapenem, meropenem, amikacin and tigecycline. Keywords : Escherichia coli, Klebsiella pneumoniae, ESBL, Pneumonia